pengaruh dana desa terhadap belanja desa bidang pembangunan infrastruktur - Muhammad Iqbal Fatwa (Fakultas Ekonomi Universitas Kadiri, 2021)
Abstracthis study aims to determine the effect of village funds on village spending in infrastructure development. The variables used in this study are village funds and village spending in infrastructure development. This research was conducted using quantitative methods with an associative approach.The population in this study is the village apparatus in sukamanah village, sukamantri village and babakan village, cisaat sub-district, sukabumi district, the sample collection in this study is the saturated sample technique. Data collection techniques by distributing questionnaires, data analysis techniques using the classic assumption and regression tests.The results of this study indicate: the independent variable is the village fund and the dependent variable is the village expenditure in infrastructure development shows partially the village fund variable influences the village expenditure in infrastructure development. Keywords: village funds, village spending in infrastructure development